2017
DOI: 10.1016/j.annals.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Not such smart tourism? The concept of e-lienation

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 73 publications
3
81
0
5
Order By: Relevance
“…Echoing Mehraliyev et al's [21] study, we believe that the potential negative effects of smart tourism on tourists should be further investigated. Prior research included alienation and authenticity to study the negative experience brought by ICT [33]. Another area of concern may be the protection of customer privacy.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Echoing Mehraliyev et al's [21] study, we believe that the potential negative effects of smart tourism on tourists should be further investigated. Prior research included alienation and authenticity to study the negative experience brought by ICT [33]. Another area of concern may be the protection of customer privacy.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…If social media and mobile applications increasingly blur the borders between the before and the after with the actual experience, one could question how this is reflected on the way tourists experience liminality, given that a 'connection' with the separation and the reaggregation is potentially never lost. Gretzel (2010) as well as Tribe and Mkono (2017), argued that this can affect the tourism experience by causing disengagement, disembodied experiences and a loss of sense of place, among other things. White and White (2007) and Silas et al (2016) echoed this negative affection by underlining a conflicting tension between the act of going away, and breaking the routine, and the desire or need to maintain social interaction with the home environment.…”
Section: Critical Perspectives On Liminality Tourism and Social Mediamentioning
confidence: 99%
“…This has dramatically affected not only how tourists experience places, but also how they actively construct them through personal stories, meanings and values (Ibid; Jaimangal-Jones, Pritchard, & Morgan, 2010;Pritchard & Morgan, 2006;Gyim othy, 2013). On the other hand, if new virtual spaces of tourism (and the way such spaces relate with the physical ones) receive increasing attention in the tourism literature, it is also true that they have been investigated mostly to understand how they can be exploited by the tourism industry (Tribe & Mkono, 2017). Although recent trends in nature-based tourism have suggested an increasing demand for the use of technology and mobile-based applications (Elmahdy, Haukeland, & Fredman, 2017), studies by Dickinson et al (2014), Dickinson, Hibbert, and Filimonau (2016), and Silas, Løvlie, and Ling (2016) have detected a perceived need to 'disconnect' from devices that dominate everyday life; this confirms dilemmas regarding the value of connectivity against a willingness to 'get away'.…”
Section: Introductionmentioning
confidence: 99%
“…Similar neurological research has shown that people who are over-reliant on satellite navigation systems for way-finding (say, back to the hotel or to a restaurant highly rated on Tripadvisor) tend to perform worse at finding their way in the absence of their digital aid than those who rely on paper maps (McCullough and Collins, 2019). Parallel research in tourism has argued that this 'smart' technology-enabled tourist may run the risk of alienation (or "e-lienation", to use the term coined by Tribe and Mkono, 2017) from their surroundings and missing out on potentially enriching experiences offered by the tourism destination. All in all, this should be rather worrying news for aspiring and existing smart tourism destinations.…”
mentioning
confidence: 99%